YMCA healthy back video - Bratt, Diane; Hanlon, Tom (Illinois : Human Kinetics, 2007)
Demonstrates correct techniques for all of the floor exercises included in the YMCA Healthy Back Book. This video shows proper form for each exercise and how to conduct exercises with a group. Also covers incorrect stretching techniques, first aid measures, and healthy back positions while standing, sitting, sleeping, driving, and lifting
A proven program from the world leader in back care education
Title from title screen
Presenter: Lynne Barnes
Keywords: Backache -- Exercise therapy; Exercise therapy; Physical fitness